Mutual Influences of New Julfa and Isfahan Mural Paintings in the 17th Century - Babayan, Ani (Armenian Folia Anglistika, 2009)
The article illustrates evidence about the mutual influence of the mural paintings in New Julfa and Isfahan mural paintings in the 17th century. The careful examination of the mural paintings in both spiritual and secular buildings reveal technical similarities between Isfahan and New Julfa trends of the time.